Genet et l’Eros Détective : Pilorge, Weidmann - Christine Marcandier (Criminocorpus)
Jean Genet is, like many writers of his generation, a great reader of Detective, in which he finds many subjects of his works (Les Bonnes). They also shape a legendary figuration of heroes of news items, elected in a properly eroticized pantheon of crime. This article proposes to study the way in which photography, its layout as its seriality, informs and innervates Genet’s texts and novels, around two disjunctive figures, one in overflow, Eugen Weidmann, the other in hollow, Maurice Pilorge, both matrices of the work.